Upaya Pencegahan Penyakit Karies Dan Periodontal Pada Lansia Penderita Diabetes Mellitus Di Panti Sosial Tresna Werdha Budi Sejahtera II Martapura Kabupaten Banjar Propinsi Kalimantan Selatan - Naning Kisworo Utami; Metty Amperawati; Siti Sab’atul Habibah; Mutiara Khairunnisa; Nabila Shafa Nuraini; Umi Nurul Fadilah (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2024)
The results of the study conducted from 34 elderly people with diabetes mellitus at the Tresna Werdha Budi Sejahtera II Martapura Social Home, Banjar Regency, South Kalimantan Province, obtained results and from 34 (100%) respondents experienced tooth loss due to cavities and shaky teeth, and none of the respondents had healthy periodontal tissue, from the results of the examination obtained as many as 30 (88.24%) respondents experienced pocket 4-5 mm, 2 (5.88%) respondents experienced bleeding gums and 2 (5.88%) respondents had tartar that needed to be treated for periodontal tissue in the elderly (Utami, NK, et al., 2018). The purpose of community service is to carry out: Efforts to Prevent Caries and Periodontal Disease in the Elderly with Diabetes Mellitus at the Tresna Werdha Budi Sejahtera II Martapura Social Home, Banjar Regency, South Kalimantan Province. The number of residents is 61 elderly people located at the Tresna Werdha Budi Sejahtera II Martapura Social Home, Banjar Regency, South Kalimantan Province. During community service activities, 47 elderly people who suffer from diabetes mellitus responded. The results obtained were that 23 respondents (48.9%) had a ≤ number of teeth 6 teeth, 35 respondents (74.5%) who did not caries and based on periodontal disease with the most score of 0 were 23 respondents (48.9%), this was because most of the respondents no longer had teeth (toothless). It is recommended that dental care and tartar cleaning are needed for the elderly at the Tresna Werdha Budi Sejahtera II Martapura Social Home, Banjar Regency, South Kalimantan Province. This is to reduce the number of dental pain and tooth loss in the elderly.